Home Numeracy Environment and Counting Skills: A Descriptive Study in Cuban Preschoolers at Age 4 Years - Yaser Ramírez-Benítez; Carlos Sebrango; Shawn L. Carlson; Natalia Józefacka; Linda Pagani (SAGE Open)
Numerous international studies have reported the importance of the home numeracy environment in promoting early math skills in preschool children; however, there is a lack of research in the Cuban context. The present descriptive study investigated the relationship between counting skills of 100 4-year-old Cuban preschoolers and the influence of formal and informal activities used in the home numeracy environment in Cienfuegos, Cuba. Results indicated that 58% of children were able to identify between five and eight objects on a counting task. Binary logistic regression revealed that maternal education was the only factor that significantly predicted children’s counting abilities. In semi-structured interviews with mothers, it was found that most (68%) used three methods to promote counting skills, including television (informal method), assistance from older siblings, and workbooks (formal method). Multivariable logistic regression indicated that both television and workbooks predicted children’s counting skills. Among mothers who were unaware that their child could count (32%), television was identified as the primary source of how their child learned to count. The analysis of the home numeracy environment of the Cuban families studied revealed the frequent use of formal methods to promote cardinality principles in 4-year-olds. Mother’s education was also found to be a significant predictor of counting skills. The use of informal activities, such as television and mobile phones, was frequent. It is necessary to avoid passive educational methods and to increase the active involvement of adults to promote the development of counting skills.